2021
DOI: 10.1108/bfj-05-2021-0536
|View full text |Cite
|
Sign up to set email alerts
|

Do young consumers care about ethical consumption? Modelling Gen Z's purchase intention towards fair trade coffee

Abstract: PurposeA global shift in ethical/sustainable purchase drivers highlights Generation Z (persons aged 15–24) as an important market for producers and marketers. Although much research has touched on fair trade consumption, very little has focused on Gen Z's consumption patterns. This study provides insights into and implications of younger consumers' motivations in ethical/sustainable consumption.Design/methodology/approachThis research examines Gen Z's purchase intention towards fair trade coffee with the theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 71 publications
1
24
0
Order By: Relevance
“…1 ( May 2022) with a mean rating of 2.87, which means that some Gen Z are conscious about the price even if the product is sustainable. A study conducted about the ethical consumption of Gen Z revealed that Gen Z's intention to buy was signi�icantly in�luenced by the product interest and subjective norm (Robichaud & Yu, 2021). Another study of sustainable green purchases stated that Gen Z's environmental concern, perceived consumer effectiveness, environmental citizenship, and collectivism are strong antecedents of green and sustainable purchases (Casalegno, Candelo, & Santoro, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…1 ( May 2022) with a mean rating of 2.87, which means that some Gen Z are conscious about the price even if the product is sustainable. A study conducted about the ethical consumption of Gen Z revealed that Gen Z's intention to buy was signi�icantly in�luenced by the product interest and subjective norm (Robichaud & Yu, 2021). Another study of sustainable green purchases stated that Gen Z's environmental concern, perceived consumer effectiveness, environmental citizenship, and collectivism are strong antecedents of green and sustainable purchases (Casalegno, Candelo, & Santoro, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…However, one of the most significant obstacles to achieving these goals is the high price of FT coffee (De Pelsmacker and Janssens, 2007;Lappeman et al, 2019). This barrier can be overcome through the expansion of the range of FT coffee (Cailleba and Casteran, 2010), the utilization of price as an indicator of its quality (Rombach et al, 2021), or the better dissemination of its ethical implications (Robichaud and Yu, 2022). Thus, on the one hand, FT coffee managers should offer higher ranges of products, from premium FT coffee brands to competitively priced FT coffee (Cailleba and Casteran, 2010).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…This generation is aware of climate change, is willing to take action to protect the environment, and is sure to do so (Robichaud & Yu, 2021; Tewari et al, 2022). Web news travel fast, and has become a driving force to raise awareness of problems, including social ones, and to organise protest events (Haynes, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…An interesting characteristic of Gen Z is its appreciation of being evaluated to improve their skills, capabilities, and knowledge. This seems to be one of the reasons why they are not afraid to "put their name" to what they believe, or to be active and to participate in public and social life (Montana & Pettit, 2008) This generation is aware of climate change, is willing to take action to protect the environment, and is sure to do so (Robichaud & Yu, 2021;Tewari et al, 2022). Web news travel fast, and has become a driving force to raise awareness of problems, including social ones, and to organise protest events (Haynes, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%